2022
DOI: 10.53660/conj-s15-1152
|View full text |Cite
|
Sign up to set email alerts
|

Pulp stones following orthodontic treatment: a case-control study

Abstract: The aim of this study was to analyze the incidence of pulp stones (PS) after orthodontic treatment. With a case-control design, 49 patients from a private orthodontic clinic in Curitiba, PR, Brazil, of both sexes, aged between 14 and 26 years, undergoing orthodontic intervention between the years 2000 and 2020, participated. Premolars and molars were analyzed from initial and final panoramic radiographs. Demographic and clinical data were collected from the patients’ medical records. After the initial descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 16 publications
3
6
0
Order By: Relevance
“…Generally, it has been reported that as age increases, the frequency of pulp stones also increases [31], whereas a study on orthodontic patients revealed no association between pulp stones and age [27]. On the other hand, our results showed a negative association between age and the frequency of pulp stones, which was in agreement with the results of Ertas et al [25].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Generally, it has been reported that as age increases, the frequency of pulp stones also increases [31], whereas a study on orthodontic patients revealed no association between pulp stones and age [27]. On the other hand, our results showed a negative association between age and the frequency of pulp stones, which was in agreement with the results of Ertas et al [25].…”
Section: Discussionsupporting
confidence: 91%
“…In this study similar to several studies, there was no statistically discernible difference in the incidence of pulp stones before orthodontic treatment among genders [25][26][27]; in contrast, Afsari et al, in a retrospective cross-sectional study, investigated the number of pulp stones prior and following to orthodontic treatment using radiographs of patients undergoing orthodontic and nonorthodontic treatment. They found a significant relationship between gender and pulp stones because females had considerable changes in the number of pulp stones [30].…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations